Immobilization and Biochemical Properties of Purified Xylanase from Bacillus amyloliquefaciens SK-3 and Its Application in Kraft Pulp Biobleaching - Sharad Kumar; Izharul Haq; Ashutosh Yadav; Jyoti Prakash; Abhay Raj (Journal of Clinical Microbiology and Biochemical Technology - Peertechz Publications, 2016)
In the present study, we studied the production and immobilization xylanase from Bacillus amyloliquefaciense strain SK-3. Isolate produced highest xylanase activity (56.2±1.6 IU/mol) at pH=8 and 40°C after 48 h incubation in presence of 1% wheat bran. Immobilization studies of purified xylanase showed that 3.0% sodium alginate and 0.2 M calcium chloride was found to be optimum. Characterization of immobilized beads by SEM and FTIR showed significant changes on the surface morphology and structure. The immobilization increases the time reaction for xylan degradation from 15-30 min and pH activity 8.0 to 9.0 whereas temperature 60-70°C with reference to free enzyme. After immobilization, thermostability of enzyme increased and retained more than 70% of its original activity after 5 h at 50°C as compared with free enzyme which showed only 20% of residual activity. Also, immobilized enzyme showed better storage stability and reusability. Overall performance of immobilized enzyme has attractive biochemical properties that make it a potential promising candidate for application in the kraft pulp pretreatment.